LABA AKUNTANSI, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP HARGA SAHAM DI BURSA EFEK INDONESIA - Gunarso, Pujo (University of Merdeka Malang, 2014)
Research data observed in 2008-2010 coincided with the global financial crisis that caused the stock price to decline and could trigger the companies listed in Indonesia Stock Exchange to perform income smoothing practices, with the condition of the researcher wanted to examine the effect of variable earnings, leverage and firm size on stock prices. The purpose of this study was to analyze the effect of accounting earnings , leverage and firm size on stock prices of public companies listed in the Indonesia Stock Exchange. The method of data analysis used was multiple linear regression analysis. The results showed that some of the first findings of accounting earnings and firm size significantly affected stock prices. Both leverages did not significantly affect the stock price. The empirical results showed that the higher the accounting profit and the size of the company were, the higher the price of shares outstanding was, and conversely the smaller the size of the company's stock price was, the less the price of shares outstanding was. The results of this study supported the theory and the researches done by Ball Brown (1968),Â Susan (2008), Sasongko Wulandari (2006), Daniati Suhairi (2006).